A Scoping Review of Needs and Barriers to Achieving A Livable Life among Refugees with Disabilities: Implications for Future Research, Practice, and Policy. Issue 3 (4th May 2023) - Rfat, Mustafa; Zeng, Yingying; Yang, Yibin; Adhikari, Kusum; Zhu, Yiqi
ABSTRACT: Purpose: Refugees with disabilities are extremely vulnerable, yet little is known about their needs and barriers to achieve better wellbeing. This scoping review aims to synthesize published research on experiences among refugees with disabilities to identify gaps and priorities to inform future research and action plans amid the global refugee crisis. Method: We searched 15 databases and included articles published in English between 2000 and 2022. Studies were included if they were empirically based peer-reviewed studies with a focus on disabled refugees and asylum seekers. Articles were excluded if they were: (a) review studies, (b) solely focused on mental health issues, (c) focused on non-refugee populations, (d) medical-related topics. Studies were each reviewed independently by two researchers. Data from the included articles were charted, interpreted, and synthesized. Results: We identified 34 relevant studies. Findings indicate that refugees with disabilities have diverse needs, including education, healthcare, employment, social benefits, and social connections and social acceptance. However, systematic barriers, such as discrimination at both policy and interpersonal levels, legal issues, and poverty, prevent these needs from being met. Discussion: This scoping review demonstrates the lack of sufficient and appropriate resources and services catering to the diverse needs of refugees with disabilities. Further quantitative and/or mixed-method research is needed to generate large-scale policy intervention. Future policies and programs should focus on institutional arrangements and advocacy efforts to facilitate disabled refugees' access to professional and inclusive healthcare services, with other supportive social services provided.